THE CIRCUMSTANCES OF HUMAN RESOURCES IN PUBLIC SECTOR BANKS AFTER MERGING IN INDIA - Rao, L. Prasada; B, Charwak; P, Vijaya Kumar (International Journal of Psychosocial Rehabilitation, 2019)
There is heated debate over the need for a merger of banks and the consequences. Indeed the appearance of the banking sector has changed significantly since the financial reforms. During this period, the country’s banking sector was undergoing new challenges. It has reached international standards beyond many milestones. Simultaneously there were many crises. To overcome situations, the government has opened the door for the entry of new private banks. When private banks have established, banking quality is likely to be enhanced by competition among banks. Due to its competitiveness, banks in a government sector dire prerequisite to give an equal game to private banks and require banking reforms. As part of the banking reforms, the public sector bank has merged. However, in doing so, the management would consider the circumstance of human resources and other issues because its effect on human resources is enormous. This research paper will discuss what impact on human resources and other issues when it comes to merged banks.